Theoretical Estimation of Maximum Ellipsoidal Magnitude of a Low-Viscosity Droplet in a Parallel Gas Stream. (15th July 2015) - Wang, Z.-B.; Bai, H.-F.; Xia, J.-X.; Zhong, H.-Q.; Li, Y.-C.
Abstract : Maximum ellipsoidal magnitude of the droplet is an important basic parameter for calculating drag force, droplets axial-velocity and dispersed-phase pressure gradient in an annular-mist pipe flow. An analytical correlation to predict the maximum ellipsoidal magnitude of a low-viscosity droplet in a parallel gas stream based on energy conservation and volume conservation. Stagnant pressure distribution on droplet surface is revised from Flachsbart's formula. The proposed correlation has clear physical meaning and easy to use. The correlation captures the deformation mechanism with an average absolute percent error of 9.53%. The effect of stagnant pressure distribution on the proposed correlation's accuracy is discussed.